Physical and chemical changes during fruit development and flowering in pomegranate (Punica granatum L.) cultivar Hicaznar grown in Antalya region - Gozlekci S.; Kaynak L. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
In this study, flowering, fruit setting and fruit growing characteristics of Hicaznar grown in Antalya conditions, which is one of our important standard cultivars, were examined. At the same time some interactions between some physical and chemical changes which occur during fruit growing and developing periods were researched. According to the results, the total number of flowers that blossomed on the examined trees, which were 10 years old, varied between 2184-2508. 77.68-86.20 per cent of the flowers were determined as unfertile (A type) and 13.58-22.32 per cent were determined as fertile (B type) flowers. While fruit setting rates of total flowers on the examined trees varied between the values of 7.59 per cent and 16.07 per cent, fruit setting of total fertile (B type) flowers varied between the values of 44.0-71.99 per cent. While fruit growth was fast at the beginning of growing period, it slowed down afterwards. A sigmoid, thus, fruit growth curve was obtained.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)